Culturally Responsive Learning : Linguistic Landscape Study of MINHA Tebuireng Jombang, Indonesia - Wahyuni, Lilik; Faizi, Ahmad; Islahuddin, Islahuddin; Sohnui, Suhailee; Novitasari, Meisya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to explore the learning of various values through the MINHA Islamic linguistic landscape, the learning of exemplary values of figures through the linguistic landscape of MINHA figures, and the learning of multicultural communication from information boards and sign names. The research employed Linguistic Landscape Research with a qualitative approach. The linguistic data used in this study were obtained from images containing written text and videos providing information about Islamic history, figures, and guidelines. The data collection methods included observation and interviews. The findings revealed that three groups of linguistic features could serve as educational tools in MINHA, including linguistic features related to Islam, characters, and instructions for using MINHA and its facilities. The diverse values embedded in these linguistic features can enhance the effectiveness of learning by catering to students with varied backgrounds. The use of language in public spaces, such as in MINHA, constitutes a form of Linguistic Landscape, which may manifest as stickers on buildings in formal or informal settings. Linguistic Landscape (LL) serves as a tool to promote multilingualism and highlight the benefits of language.